Transcription Factor DLX5 Promotes Hair Follicle Stem Cell Differentiation by Regulating the c-MYC/microRNA-29c-3p/NSD1 Axis - Lin, Bojie; Zhu, Jiangying; Yin, Guoqian; Liao, Mingde; Lin, Guanyu; Yan, Yuyong; Huang, Dan; Lu, Siding (Frontiers in Cell and Developmental Biology, 2021)
Introduction: Adult stem cell function has been one of the most intensively explored areas of biological and biomedical research, with hair follicle stem cells serving as one of the best model systems. This study explored the role of the transcription factor DLX5 in regulating hair follicle stem cell (HFSC) differentiation. Methods: HFSCs were isolated, characterized, and assessed for their expression of DLX5, c-MYC, NSD1 and miR-29c-3p using RT-qPCR, Western blot analysis, or immunofluorescence. Next, the ability of HFSCs to proliferate as well as differentiate into either sebaceous gland cells or epidermal cells was determined. The binding of DLX5 to the c-MYC promoter region, the binding of c-MYC to the miR-29c-3p promoter region, and the binding of miR-29c-3p to the 3’-UTR of NSD1 mRNA were verified by luciferase activity assay and ChIP experiments. Results: DLX5 was highly expressed in differentiated HFSCs. DLX5 transcriptionally activated c-MYC expression to induce HFSC differentiation. c-MYC was able to bind the miR-29c-3p promoter and thus suppressed its expression. Without miR-29c-3p mediated suppression, NSD1 was then able to promote HFSC differentiation. These in vitro experiments suggested that DLX5 could promote HFSC differentiation via the regulation of the c-MYC/miR-29c-3p/NSD1 axis. Discussion: This study demonstrates that DLX5 promotes HFSC differentiation by modulating the c-MYC/miR-29c-3p/NSD1 axis and identifies a new mechanism regulating HFSC differentiation.